Effect of different COVID-19 vaccines on some biomarkers in diabetics - Munther Kamil Oudha; Ahmad Shandookh Hameed; Lina Abdullah Naser (University of Thi-Qar Journal of Science, 2023)
After the emergency approval of different COVID-19 vaccines the administration of millions of doses, many concerns arise for adverse effects, especially in vulnerable groups such as diabetics. In this study, we investigate what effects different COVID vaccines could have on several biomarkers in diabetic patients and whether that raises a concern for this group or not. Materials and methods: this study includes two groups of diabetics each group consists of 20 participants ; One of the groups under study, where they received the COVID-19 vaccine either AstraZeneca or Pifizr-BioNTech vaccine and the other groups were controlled or the Pfizer-BioNTech vaccine, the other group-the control group- did not take any vaccine. Blood samples were taken from both groups about a week after the first dose and statistical studies were conducted on the results. Results: Noticed an increase in all biomarkers. Increase in RBS could simply be due to immune response, same thing could be said for the CRP increase. Ferritin increase was not important; it was only apparent in three patients and that could be due to active infection. The increase in D-dimer levels was apparent in all patients and that raises the biggest concern. Conclusion: the biggest issue was seen in the rising of D-dimer levels because it raises concern about clotting disorders and heart disease which is already a concern for diabetic patients. Further investigation should be done and careful monitoring for clotting risks is necessary after the vaccine.